(untitled) (Global Journals of Research in Engineering, 2022)
A superpave system is a way to specify the components in asphalt pavements that perform better than average A new approach has been created for specifying the asphalt ingredients in asphalt concrete as part of the Strategic Highway Research Program SHRP The shorthand name for this technology is superpave which stands for high performance asphalt pavements The research that resulted in the creation of this new system was started because prior to the invention of superpave it was challenging to connect the dots between the performance of the pavement and the findings from laboratory analysis in the previous systems